Fraccionamiento del poder impositivo - Jorge C. Ávila (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2009)
– The essay provides support to the hypothesis that financing of provincial public spending through national transferences leads to overspending. We rest on persuasive economic and politicoinstitutional arguments. Fiscal illusion and the Leviathan model help to explain the overspending. And cartelization of tax collection helps to explain why governors are so reluctant to decentralize this task. We conclude that a fiscal organization closer to that of a confederation would be desirable. Two ways of organizing fiscal relations between the Nation and the provinces are considered. One way consists of paying for national spending by means of periodic provincial transferences; control of public spending by tax-payers would be the greatest possible in this scenario, though leaving national financing in provincial hands could be a risky affair. Another way consists of allowing the Nation some taxing power and incorporating constitutional restrictions as regards the kinds of public goods the national government is permitted to provide.
Keywords: 330